Biological Fabrication: Future Perspectives on Biological Fabrication and Material Farming (Small Methods 1/2019). Issue 1 (7th January 2019) - Natalio, Filipe
Abstract : In article1800136, Filipe Natalio discusses the emerging fields of biological fabrication and material farming using organisms as biofactories. Understanding organisms' paths and combining with their molecular design, it is possible to fabricate new composite materials with end‐functionalities and improved properties that surpass traditional surface functionalization methods. The state‐of‐the‐art achievements and future perspectives for this field are discussed.